A Study on Occupational Stress among Faculty Members of Private B Schools in Kollam District, Kerala - C.G, Manojkrishnan.; M, Aravind. (International Journal of Psychosocial Rehabilitation, 2020)
Teaching has become stressful due to the changing academic scenario. The core objectives of this study were to identify the factors causing occupational stress and also to identify the important symptoms of occupational stress as experienced by the faculty members. The researchers did a survey among 52 faculty members working in Kollam district. The collected data was statistically tested with tools such as weighted average mean, Pearson’s Chi-Square test, Multi Dimensional Scaling Alscal Model, Euclidean Distance model etc. Based on the analysis it is understood that the variables such as Show – Off’s during the office meetings, anxiety about career and future, travel time, inability to find time for oneself, Inability to grab the right opportunity Lack of recognition of work, Uncertainty about career opportunities, inability to live up to own expectation, Thoughts about work even while at home are some of the important stressors. Teachers experience the following physical symptoms like Head ache and neck ache, muscular aches & tension and fatigue. They have also experienced mental symptoms like apathy/ Loss of interest in work and frequent mood swings. Yoga, Meditation, Time Management, Bio Feedback, Proactive planning etc suggested as methods to mitigate stress. The study has been concluded by mentioning how this research work can be beneficial to other researchers.